Answer:
She applied the addition property of equality to isolate the variable term wrong.
C
The third one.
Explanation:
Examine Morgan’s work to solve the equation.
-8m + 6 - 2m = 9(3m + 4) + 5m
1. -8m + 6 - 2m = 27m + 36 + 5m
2. -10m + 6 = 32m + 36
3. 6 = 22m + 36
4. -30 = 22m
5.
−15
11
= m
What is the error in Morgan’s work?
She did not distribute the 9 to both terms inside the parentheses.
She combined the like terms on each side of the equation wrong.
She applied the addition property of equality to isolate the variable term wrong.
She applied the division property of equality instead of the multiplication property of equality to solve for the variable.